2023
DOI: 10.1088/1755-1315/1222/1/012029
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability of Agricultural Productivity of Potato Crop in Desert Soils and Evaluation of Water Productivity Under Drip Irrigation System with Future Climate Changes

Abstract: A field experiment was conducted during the spring season 2020 in Karbala proving/ Al-Sharia Distrit, located at latitude N 32° 42' 13.8" and longitude E 43° 54' 36.6" and at an altitude of 27 m above sea level. The experiment included a study of two factors: the first, Irrigation Interval, three treatments were used: irrigation treatment every 2 days, Irrigation treatment every 4 days, and Irrigation treatment every 6 days. The second factor is the addition of soil conditioners, in which four treatments were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Although the texture of the area is coarse and medium coarse in general, a noticeable increase was observed in some areas of the farm, especially in the areas of palm and pomegranate cultivation, as well as greenhouses as well as the fields of alfalfa where this rise is attributed to the soil management practices and reclamation processes applied to those areas, including the addition of organic materials and improvers, which led to this rise in values compared to the rates of barley lands and unused lands of the farm so far. (16,38,44,45). Soil water infiltration: Table (1) shows that there are high differences in the values of the cumulative infiltration according to the type of cultivated vegetation, whose value ranged in 3600 seconds between 5.18 -17.34 cm h -1 , and that the lowest cumulative infiltration in the soil was under the cover of greenhouse cultivation, followed by the lands that were prepared for the cultivation of vegetables, while the highest value was recorded in the fallow and barren lands, and the reason is due to the accumulation of salts in some of the fallow lands, as well as the lack or of organic matter, which leads to a decrease in the soil holding capacity for water and consequently the high value of the infiltration as well as the main effect on the soil of the study area, where those resulted was also found (3,5,6,19,51).…”
Section: Bulk Densitymentioning
confidence: 99%
See 1 more Smart Citation
“…Although the texture of the area is coarse and medium coarse in general, a noticeable increase was observed in some areas of the farm, especially in the areas of palm and pomegranate cultivation, as well as greenhouses as well as the fields of alfalfa where this rise is attributed to the soil management practices and reclamation processes applied to those areas, including the addition of organic materials and improvers, which led to this rise in values compared to the rates of barley lands and unused lands of the farm so far. (16,38,44,45). Soil water infiltration: Table (1) shows that there are high differences in the values of the cumulative infiltration according to the type of cultivated vegetation, whose value ranged in 3600 seconds between 5.18 -17.34 cm h -1 , and that the lowest cumulative infiltration in the soil was under the cover of greenhouse cultivation, followed by the lands that were prepared for the cultivation of vegetables, while the highest value was recorded in the fallow and barren lands, and the reason is due to the accumulation of salts in some of the fallow lands, as well as the lack or of organic matter, which leads to a decrease in the soil holding capacity for water and consequently the high value of the infiltration as well as the main effect on the soil of the study area, where those resulted was also found (3,5,6,19,51).…”
Section: Bulk Densitymentioning
confidence: 99%
“…They describe the capability of soil to maintain crop productivity, environmental quality, and support plant, animal, and human health. The term "soil biological health" can be used to refer to the biological function of soil in relation to plant growth, yield and productivity (45). The use of the term "soil health" emphasizes that a soil ecosystem requires maintenance and conservation to maintain the biodiversity and biological activity.…”
Section: Introductionmentioning
confidence: 99%